2022
DOI: 10.1021/acsami.2c05457
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Aspects for the Design of a Bicarbonate Zero-Gap Flow Electrolyzer for the Conversion of CO2 to Formate

Abstract: CO2 electrolyzers require gaseous CO2 or saturated CO2 solutions to achieve high energy efficiency (EE) in flow reactors. However, CO2 capture and delivery to electrolyzers are in most cases responsible for the inefficiency of the technology. Recently, bicarbonate zero-gap flow electrolyzers have proven to convert CO2 directly from bicarbonate solutions, thus mimicking a CO2 capture medium, obtaining high Faradaic efficiency (FE) and partial current density (CD) toward carbon products. However, since bicarbona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 56 publications
(96 reference statements)
0
18
0
Order By: Relevance
“…The experimental conditions were set based on the optimization study for bicarbonate electrolysis performed recently by our group . From this study, the most optimal flow rate, temperature, and CD to achieve the highest energy efficiency were chosen.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental conditions were set based on the optimization study for bicarbonate electrolysis performed recently by our group . From this study, the most optimal flow rate, temperature, and CD to achieve the highest energy efficiency were chosen.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Although direct electrochemical conversion of the bicarbonate anion has been reported, it has been a topic of discussion within the community whether bicarbonate was the substrate of the electrochemical reaction or solely played the role of carbon donor by providing CO 2 (derived from the equilibrium with water) to the surface of the electrode (or both). , Albeit neither confirming nor discarding any line of thought, several more recent studies showed how promoting the release of CO 2 from bicarbonate in situ the electrolyzer improved to a great extent both the FE and partial CD of the bicarbonate electrolysis. It was found that this release could be promoted by using a bipolar membrane (BPM) in combination with a zero-gap flow electrolyzer. Indeed, experimental results demonstrated that bicarbonate is more efficiently converted to CO 2 thanks to the water dissociation (1) occurring in the BPM once the potential is applied (H + is released toward the catholyte, and OH – is released toward the anolyte) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, after conversion, the alkalinity of the solution is regenerated such that it can be reused as a capture solution . However, bicarbonate electrolyzers are still far from being optimized and cannot yet compete in terms of energy efficiency with pure CO 2 electrolyzers. , The main reason is the high proton donor ability of bicarbonate leading to undesired coreactions like the hydrogen evolution reaction (HER) and the mass transfer limitations in the electrode–electrolyte interface since CO 2 needs to be delivered from the equilibrium of bicarbonate with water. , In this context, there is increasing interest in optimizing this combined capture and conversion process to make it more feasible . For instance, a promising option to optimize the capture step is to decrease the operational time to capture a certain amount of CO 2 (g CO 2 h –1 ) in the form of bicarbonate .…”
Section: Introductionmentioning
confidence: 99%
“…33,34 In this context, there is increasing interest in optimizing this combined capture and conversion process to make it more feasible. 35 For instance, a promising option to optimize the capture step is to decrease the operational time to capture a certain amount of CO 2 (g CO 2 h −1 ) in the form of bicarbonate. 36 On the other hand, a strategy to increase the energy efficiency of the bicarbonate electrolyzer is to inhibit the proton donor ability of bicarbonate and the undesired HER.…”
Section: ■ Introductionmentioning
confidence: 99%